INTERSECTION CULTURAL VALUE, NATIONALISM, AND COMMODIFICATION BEHIND THE GARUDA CHAIR AS JEPARA’S SIGNATURE INDUSTRIES - Fajarwati, Ade Ariyani Sari; Caroline, Octaviana Sylvia; Wulandari, Laura Andina (Humaniora, 2020)
The purpose of the research was to identify the cultural value and nationalism behind the Garuda chair and to compare it with another style that had more sellable value as commodities. The research used the qualitative descriptive methodology used literature, observation, site visit, and interview data to analyzed. In conclusion, the Garuda chair has the potential to become an Indonesian commodity in the furniture market and international community by promoting the cultural value behind it and the effectiveness of material using for the chair.